Hormone levels in neonatal hair reflect prior maternal stress exposure during pregnancy. (April 2016) - Kapoor, Amita; Lubach, Gabriele R.; Ziegler, Toni E.; Coe, Christopher L.
Highlights: Hormones in hair reflect cumulative endocrine activity while the hair was growing. Hair hormones measured in neonates can be employed to assess the prenatal hormone environment. LC/MS/MS methods permitted seven hormones to be determined in hair. Prenatal stress impacted the levels of cortisol and gonadal hormones in infant hair. Abstract: Hormones present in hair provide summative information about endocrine activity while the hair was growing. Therefore, it can be collected from an infant after birth and still provide retrospective information about hormone exposure during prenatal development. We employed this approach to determine whether a delimited period of maternal stress during pregnancy affected the concentrations of glucocorticoids and gonadal hormones in the hair of neonatal rhesus monkeys. Hair from 22 infant monkeys exposed to 5 weeks of gestational disturbance was compared to specimens from 13 infants from undisturbed control pregnancies. Using an LC/MS/MS based technique, which permitted seven steroid hormones to be quantified simultaneously, we found 2 hormones were significantly different in infants from disturbed pregnancies. Cortisol and testosterone levels were lower in the hair of both male and female neonates. Maternal hair hormone levels collected on the same day after delivery no longer showed effects of the disturbance earlier during pregnancy. This study documents that a period of acute stress, lasting for 20% of gestation, has sustained effects on the hormones to which a developing fetus is exposed.